CD47 Overcomes Early Loss of Pancreatic Islet Grafts Transplanted Intraportally. (July 2018) - Shrestha, Pradeep; Bowen, William S; Batra, Lalit; Tan, Min; Yolcu, Esma S; Shirwan, Haval
Abstract : Introduction and Objective: Intraportal islet transplantation is an effective curative therapy for type 1 diabetes. However, a significant mass of islets is eliminated immediately post-transplantation by innate immune mechanisms described as instant blood-mediated inflammatory reaction (IBMIR). CD47 regulates various innate immune cell functions involved in IBMIR. In particular, the engagement of CD47 with its receptor SIRPa expressed on phagocytes blocks phagocytosis. We herein tested if transient display of a novel chimeric form of CD47, SA-CD47, protein on the surface of islets enhances engraftment following intraportal transplantation in a marginal mass model. Materials and Methods: A chimeric gene containing the extracellular domain of murine CD47 fused to a core streptavidin (SA) was constructed. SA-CD47 protein was produced in insect cells and purified using affinity chromatography. The function of SA-CD47 protein to block phagocytosis was assessed in vitro using RAW 264.7 mouse macrophages co-cultured with rat spleen cells engineered with SA or SA-CD47 proteins. To assess the role of SA-CD47 in engraftment, C57BL/6 islets were biotinylated and then engineered with equimolar amount of SA-CD47 (400 ng/125 islets) or SA as control, taking advantage of the high affinity interaction between biotin and the SA portion of CD47. Engineered islets were then transplanted intraportally into streptozotocin diabetic syngeneic mice. Animals were monitored for blood glucose levels, and the function of islet graft was assessed by an intraperitoneal glucose tolerance test (IPGTT). Results and Discussion: SA-CD47 was successfully produced, purified, and validated by flow cytometry or western blots. SA-CD47 protein was displayed on biotinylated cells and/or islets without negatively impacting the function of cells or islets. SA-CD47-engineered rat spleen cells were minimally phagocytosed by macrophages as compared with SA-engineered control splenocytes. In vivo, only 1/7 SA-engineered islet grafts achieved normoglycemia for an observation period of 80 days. In marked contrast, 7/8 SA-CD47-engineered islet grafts achieved euglycemia. Recipients transplanted with SA-CD47-engineering islets showed a comparable IPGTT response to naïve mice, demonstrating long-term, preserved function of islets. QRT-PCR and flow analyses of the liver and various lymphoid tissues early post-Tx did not reveal significant differences in various immune cells and immunomodulatory molecules between the SA and SA-CD47 groups, implicating inhibition of islet phagocytosis as the underlying mechanisms of enhanced islet engraftment and survival. Conclusion: Engineering islets with SA-CD47 protein provides a novel, effective means of preventing early loss of functional islet mass precipitated by IBMIR. Achievement of euglycemia with a minimal islet mass will help to overcome the shortage of islets from cadaveric donors and may also facilitate living donor islet transplantation. This study was funded in part by NIH (grants R21EB020107, R21AI113348, and R56AI121281)